Foreign trade university students’ opinions on computer use in English learning - Nguyen , Vu Thanh Tuyen; Do , Anh Thu (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This article focused on students’ opinions on computer use in English learning (EL). We hope that this survey could wake the awareness of the students who have not recognized computer importance, step-by-step raising their interest in computer application in their EL and at the same time, encouraging the students who have mastered computer roles to deploy them more effectively.